Artificial Intelligence dan Masa Depan Pendidikan Agama Islam: Tantangan Otoritas, Etika, dan Literasi Keagamaan Digital - Suprihatin; Sitti Aisyah; Sesti Novalina; Mona Novita (PT Cendekia Education Center, 2026)
This study explores the future of Islamic Religious Education (IRE) in the era of Artificial Intelligence (AI) by examining emerging challenges related to religious authority, ethics, and digital religious literacy. A qualitative approach employing a futures studies design with the Delphi technique was adopted to investigate plausible transformations and develop a conceptual governance framework for AI integration in IRE. Eighteen experts representing Islamic Religious Education, educational technology, artificial intelligence, digital ethics, and educational policy participated in two rounds of online Delphi inquiry using open-ended prompts. Data were analyzed through thematic analysis involving coding, categorization, pattern identification, and conceptual synthesis, while iterative validation across Delphi rounds ensured conceptual convergence. The findings indicate that AI is likely to transform IRE by redefining teachers’ roles, expanding personalized religious learning, and positioning AI as a primary mediator of religious knowledge. Four major strategic challenges emerged: shifts in epistemic authority, threats to doctrinal integrity, erosion of pedagogical ethics, and deficiencies in digital religious literacy. Based on these findings, the study proposes the AI-Mediated Islamic Religious Education Governance Framework (AIR-GOV Framework), comprising four interconnected pillars: religious authority legitimacy, pedagogical ethics, doctrinal integrity, and digital religious literacy. The framework provides a conceptual foundation for responsible AI governance in Islamic Religious Education, balancing technological innovation with the epistemological and normative principles of Islamic education.